2017
DOI: 10.1101/229591
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Estrogen receptor inhibition enhances cold-induced adipocyte beiging and glucose sensitivity

Abstract: Low estrogen states, exemplified by postmenopausal women, are associated with increased adiposity and metabolic dysfunction. We recently reported a paradox, in which a conditional estrogen receptor-alpha (ERα) mutant mouse shows a hyper-metabolic phenotype with enhanced brown/beige cell formation ("browning/beiging"). These observations led us to consider that although systemic deficiency of estrogen or ERα in mice results in obesity and glucose intolerance at room-temperature, cold-exposure might induce enhan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
(93 reference statements)
0
1
0
Order By: Relevance
“…For decades, thermogenic, anorexigenic, and anti-dipsogenic effects of estradiol were reported and characterized in female laboratory rodents [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. In 2019, it was reported that when female mice were housed in chronic cold stress conditions, estradiol inhibited thermogenic browning of white adipose tissue [21]. The following year, anorexigenic effect of estradiol was observed in female mice during rebound feeding [22].…”
Section: Introductionmentioning
confidence: 99%
“…For decades, thermogenic, anorexigenic, and anti-dipsogenic effects of estradiol were reported and characterized in female laboratory rodents [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. In 2019, it was reported that when female mice were housed in chronic cold stress conditions, estradiol inhibited thermogenic browning of white adipose tissue [21]. The following year, anorexigenic effect of estradiol was observed in female mice during rebound feeding [22].…”
Section: Introductionmentioning
confidence: 99%